Cultivo protegido de cultivares de alface Americana no inverno e primavera em Ponta Grossa - PR - Niesing, Priscila Cristina (2006)
The experiments were carried out in an experimental area of the Ponta Grossa State University, Parana State, Brazil in winter (experiment 1) and spring (experiment 2) of 2005/2006, with the aim to evaluate the production of two crisphead lettuce (Lucy Brown and Raider Plus) under five different environments of culture: thermo-reflective screen (Aluminet 40%), diffusive screen (ChromatiNet 40%), natural environment, low tunnel with polyethylene and under nonwowen protection (white polypropylene of 17 g/m2 grid). The experimental design for both experiments was a completely randomized with four replications in a factorial scheme 5x2 (crop systems x cultivars). For both the experiments where evaluated: the total, commercial head and outer leaves fresh matter weight (BFT, BFCab and BFS- g/m2), and the outer leaves as well as their total and marbetable head dry matter (BST and BSCab - g/m2). For experiment 2 dry matter of the outer leaves, index of the foliar area of the outer leaves (IAFS) and of the leaves of the commercial head (IAFCab) were also evaluated. In the winter of Ponta Grossa, for both the cultivars, the crop systems qith nonwowen protection and low tunnel it had an early harvest of 21 days. However, in the spring, did not have difference in the cycle of the lettuce, independent of the cultivar and the crop system. But, the commercial production were superior in relation to the winter, possibly because of the more favorable climatic conditions for the crisphead lettuce culture. Keywords: Lactuca sativa, cultivars, protected cultivation, tunnel, polypropylene, Aluminet, ChromatiNet